2017
DOI: 10.3389/fmicb.2017.01266
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Rock Phosphate Fertilization Impacts the Microbial Communities of Maize Rhizosphere

Abstract: Phosphate fertilization is a common practice in agriculture worldwide, and several commercial products are widely used. Triple superphosphate (TSP) is an excellent soluble phosphorus (P) source. However, its high cost of production makes the long-term use of crude rock phosphate (RP) a more attractive alternative in developing countries, albeit its influence on plant-associated microbiota remains unclear. Here, we compared long-term effects of TSP and RP fertilization on the structure of maize rhizosphere micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 68 publications
11
39
0
Order By: Relevance
“…Silva et al . () found that Burkholderia was enriched by the amendment of crude rock phosphate in the rhizosphere of maize plants, supporting our results. However, some less described taxa (e.g., Candidatus Pelagibacter , Trichodesmium , Neorickettsia ) have yet to be explored.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Silva et al . () found that Burkholderia was enriched by the amendment of crude rock phosphate in the rhizosphere of maize plants, supporting our results. However, some less described taxa (e.g., Candidatus Pelagibacter , Trichodesmium , Neorickettsia ) have yet to be explored.…”
Section: Resultssupporting
confidence: 90%
“…More importantly, our data indicated that Candidatus Pelagibacter, Trichodesmium, Neorickettsia, Nitrobacter, Paraburkholderia, Candidatus Solibacter and Burkholderia were the major taxa contributing to stronger capacity of solubilizing sparingly soluble Pi in bahiagrass soil. Silva et al (2017) found that Burkholderia was enriched by the amendment of crude rock phosphate in the rhizosphere of maize plants, supporting our results. However, some less described taxa (e.g., Candidatus Pelagibacter, Trichodesmium, Neorickettsia) have yet to be explored.…”
Section: Soil Microbial Taxa Contributing To the Differential P Acquisupporting
confidence: 90%
“…In both genotype, RPB additions promote a higher diversity of microorganisms compared to TSP and no phosphorus additions. This was already observed in long term studies (SILVA et al, 2017). These findings, together with the previous observations regarding genotype effect, provide evidences to support the proposed hypothesis that there is a correlation between the plant efficiency in phosphorus uptake and its rhizosphere microbiome in phosphorus mobilization and that this recruitment is potentialized in phosphorus depleted conditions.…”
Section: Rhizosphere Microbial Assembly In Phosphorus Gradientsupporting
confidence: 86%
“…The rhizosphere of IAC Imperador with L50 of RPB, showed an increase in several phyla, like Bacteroidetes, Acidobacteria, Planctomycetes and Proteobacteria compared to phosphorus depleted conditions. Changes in rhizosphere microbial community of maize was already described, showing a significant enrichment of Oxalobacteriacea (Betaproteobacteria), Burkholderiacea (Betaproteobacteria) and Bacillaceae (Firmicutes) was observed in maize rhizosphere (SILVA et al, 2017). However, considering the involvement of the rhizosphere microbiome in phosphorus mobilization a significant enrichment of binding and transport proteins is promoted under phosphorus limiting conditions in the IAC Imperador genotype.…”
Section: Rhizosphere Microbial Assembly In Phosphorus Gradientmentioning
confidence: 84%
“…Ikeda et al (2013) have only found the genera Pantoea, Bacillus, Burkholderia, and Klebsiella to occur in commercial maize seeds from the east region of the Paraná state, indicating a higher diversity of bacteria associated with maize grains in the North Central part of the same state (this work). The occurrence of the genera Massilia and Ochrobactrum have been reported in maize roots and rhizosphere (Niu et al, 2017;Silva et al, 2017). The occurrence of Modestobacter and Isoptericola genera isolates have not been described yet in maize grains.…”
Section: Discussionmentioning
confidence: 99%